2022
DOI: 10.17687/jeb.v10i1.860
|View full text |Cite
|
Sign up to set email alerts
|

Does the trust issue impact the intention to use e-wallet technology among students?

Abstract: The current research goal is to examine the impact of trust on the intention to use e-wallet services. Using the technology acceptance model (TAM) the study investigated four variables which were privacy and security, perceived ease of use, perceived usefulness, and trust for intention to use e-wallets. The study employed the quantitative research design with non-probability sampling using the purposive sampling method for data collection purposes. Through the Google survey form data were collected from the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…An empirical study showed an optimistic relationship between e-learning and PEU (Abdullah and Ward, 2016). Many researchers hypothesized that PEU for e-learning might enhance the intention of using online learning systems comprehensibly (Davis, 1989;Mailizar et al, 2021;Hossain et al, 2022). In this study, students perceive that online learning is convenient.…”
Section: Perceived Ease Of Usementioning
confidence: 74%
“…An empirical study showed an optimistic relationship between e-learning and PEU (Abdullah and Ward, 2016). Many researchers hypothesized that PEU for e-learning might enhance the intention of using online learning systems comprehensibly (Davis, 1989;Mailizar et al, 2021;Hossain et al, 2022). In this study, students perceive that online learning is convenient.…”
Section: Perceived Ease Of Usementioning
confidence: 74%
“…In order to help Malaysians during the COVID-19 pandemic, the Malaysian government periodically offers stimulus packages. These bundles under the "PRIHATIN" programme have contributed to the increased usage of E-wallet in Malaysia [2]. These include cash back offers, discounts, and loyalty points.…”
Section: Introductionmentioning
confidence: 99%

Perception on E-Wallet Application among Night Market Consumer in Lembah Klang

Nur Badriyah Kamarul Zaman,
Muhammad Haziq Hasbullah Azmi,
Wan Noranida Wan Mohd Noor
2024
ARBMS